Metabolomics reveals a lipid accumulation mechanism involving carbon allocation in Scenedesmus obliquus under norfloxacin stress. (September 2020) - Chu, Huaqiang; Ren, Li; Yang, Libin; Chen, Jiabin; Zhou, Xuefei; Zhang, Yalei
Abstract: The transformation of organic components and the mechanism of lipid accumulation under stress in an algae–antibiotic system were studied. It was found that the antibiotic norfloxacin (NOR; 5–80 mg/L) had a pronounced effect on the lipid accumulation of the cultured Scenedesmus obliquus . Upon exposure to 80 mg/L NOR, the lipid content of the algae cells increased to 30.8%, which was approximately 2-fold higher than that of the blank control culture. Metabolomics was used to identify the biochemical changes induced by NOR in S. obliquus . The tricarboxylic acid cycle and the metabolic pathways of fatty acids, starch, and amino acids significantly changed under NOR stress. This stress triggered the production of reactive oxygen species, which contributed to intracellular signaling. This led to the shifting of additional common precursors (such as pyruvate and glucose) from the starch pathway to the fatty acid synthesis pathway and resulted in increased lipid accumulation and carbohydrate downregulation. Hence, carbon allocation shifted from carbohydrates to lipids as a storage reserve. Graphical abstract: Image 1 Highlights: Norfloxacin stress on Scenedesmus obliquus lipid accumulation was obviously. Metabolic pathways of tricarboxylic cycle, fatty acids and starch were altered. Carbon allocation shifted from carbohydrates to lipids as a storage reserve. Results are useful for antibiotics wastewater with oleaginous microalgae culture.